Requirements for evidence-based management competency in healthcare: a scoping review - Elyas Sanaeifar; Elyas Sanaeifar; Elaheh Houshmand; Elaheh Houshmand; Javad Moghri; Javad Moghri; Marjan Vejdani; Seyed Saeed Tabatabaee; Seyed Saeed Tabatabaee (Frontiers in Public Health)
BackgroundIdentifying the essential skills and qualifications for evidence-based managers in healthcare is crucial for decision-makers who aim to select competent managers and design effective training programs. This study reviews the requirements, capabilities, and skills necessary for evidence-based managers in the healthcare sector to accurately utilize and implement evidence.MethodThis scoping review was conducted following the PRISMA-SCR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) guidelines. A thorough literature search was carried out using relevant keywords across the Web of Science, PubMed, and Scopus databases, with no time restrictions. The selection of articles adhered to predefined inclusion criteria. After eliminating duplicates and reviewing titles, abstracts, and full texts, six articles were included in the final analysis.ResultsThe study identified several competencies required for effective evidence-based management in healthcare, including professional and technical knowledge, leadership, personal traits and attitudes, communication skills, information management, self-management, critical thinking, research skills, and the ability to apply evidence effectively.DiscussionGiven the ongoing transformations in healthcare, including the emergence of new technologies and the generation of extensive data, evidence-based managers must continually enhance their skills to access and evaluate evidence. They should also work on improving both their interpersonal and intrapersonal skills. The authors advocate for further applied research to deepen our understanding of the competencies required for evidence-based managers within the healthcare and treatment contexts.